Ketuban Pecah Dini pada Primigravida Usia Kehamilan 37 Minggu: Sebuah Laporan Kasus - Ikram, Lucky; Zulfadli, Zulfadli (CV. Jasa Sukses Abadi, 2024)
Premature rupture of membranes (PROM) is the rupture of the amniotic membranes before delivery which is characterized by painless discharge and the patient being unable to hold it in. Preterm premature rupture of membranes can occur at or after 37 weeks of gestation and is called term PROM or prelabor rupture of membranes (PROM) and before 37 weeks of gestation or preterm PROM or preterm prelabor rupture of membranes (PPROM) PROM affects 3–15% of all pregnancies. global. PROM is associated with causes of perinatal mortality and morbidity with percentages of 18%–20% and 21.4% respectively. This study is a case report. A 24 year old female patient complained of a full term pregnancy accompanied by watery discharge. The patient complained that water was coming out, the patient realized that his trousers were suddenly wet, and suddenly this complaint was felt since 7 o'clock before administred. According to the patient's statement, the air is clear and has no smell. On physical examination, the level of consciousness was compos mentis, blood pressure 113/83 mmHg, pulse 80x/m, RR 20x/m, temperature 36.5oC, SpO2 98%. On obstetric examination, the height of the uterine fundus was 34 cm, the second part of the fetus was the buttock impression. It is located along the right back. The lowest part of the fetus's head. Convergent with the impression that the head has not yet entered the PAP. Decreased 5/5 The uterus contracts regularly, 3 times in 10 minutes, duration 30 – 40 seconds. Fetal DJJ was 141x/m and EFW was 3410. And an internal examination was carried out, on inspection a Pooling sign was obtained (+) and a nitrazine test was carried out with positive results. The patient was diagnosed as G1P0A0, 37 weeks pregnant in the 1st stage of late stage pregnancy with a history of PROM, a single live fetus in cephalic presentation. The patient's treatment consisted of giving broad spectrum antibiotics as prophylaxis and planned vaginal delivery. The treatment given was appropriate.